PENGARUH PROFITABILITAS, LEVERAGE, DAN CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2014) - Mohammad Fajar; Zulbahridar Zulbahridar; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The aim of this study was to examine the effect of Profitability, Leverage, and Corporate Governance to Tax Avoidance in Manufacturing Company Listed in Indonesia Stock Exchange Period 2012-2014. The population are all LQ45 companies in Indonesia still operation during the years 2012-2014. Based on specified criteria, the company earned 68 were used as samples in this study. Sample selection by using purposive sampling method. This study uses secondary data such as financial statements and methods of data analysis using multiple linear regression analysis. The conclusions is: Profitability and Leverage effect on Tax Avoidance. The Institutional Ownership, the proportion of independent commissioners’ board, and Audit Committe do not effect on the Tax Avoidance.Keywords : Profitability, Leverage, Corporate Governance and Tax Avoidance